A phase II study of ponatinib for prevention of relapse after allotransplantation in FLT3 internal tandem duplication mutation positive (FLT3-ITD+) acute myeloid leukemia: the PONALLO trial - Patrice Chevallier; Anne Thiebaut; Sylvie François; Sylvain Chantepie; Marie-Thérèse Rubio; Hélène Labussiere-Wallet; Eolia Brissot; Natacha Maillard; Anne Huynh; Valérie Coiteux; Maxime Jullien; Alice Garnier; et al. (Haematologica)
Not available.